Metalated graphyne-based networks as two-dimensional materials: crystallization, topological defects, delocalized electronic states, and site-specific doping - Yang, Zechao; Sander, Tim; Gebhardt, Julian; Schaub, Tobias A.; Schönamsgruber, Jörg; Soni, Himadri R.; Görling, Andreas; Kivala, Milan; Maier, Sabine (ACS nano, 2020)
Graphyne-based two-dimensional (2D) carbon allotropes feature extraordinary physical properties; however, their synthesis as crystalline single-layered materials has remained challenging. We report on the fabrication of large-area organometallic Ag−bis-acetylide networks and their structural and electronic properties on Ag(111) using low-temperature scanning tunneling microscopy combined with density functional theory (DFT) calculations. The metalated graphyne-based networks are robust at room temperature and assembled in a bottom-up approach via surface-assisted dehalogenative homocoupling of terminal alkynyl bromides. Large-area networks of several hundred nanometers with topological defects at domain boundaries are obtained due to the Ag-acetylide bonds’ reversible nature. The thermodynamically controlled growth mechanism is explained through the direct observation of intermediates, which differ on Ag(111) and Au(111). Scanning tunneling spectroscopy resolved unoccupied states delocalized across the network. The energy of these states can be shifted locally by the attachment of a different number of Br atoms within the network. DFT revealed that free-standing metal−bis-acetylide networks are semimetals with a linear band dispersion around several high-symmetry points, which suggest the presence of Weyl points. These results demonstrate that the organometallic Ag−bis-acetylide networks feature the typical 2D material properties, which make them of great interest for fundamental studies and electronic materials in devices.
Gesehen am 28.01.2021